Coagulation, Fibrinolytic and Platelet Function in Patients on Long-Term Therapy with Aspirin 300 mg or 1200 mg Daily Compared with Placebo - Hampton, K K; Cerletti, C; Loizou, L A; Bucchi, F; Donati, M B; Davies, J A; de Gaetanox, G; Prentice, C R M (Thrombosis and Haemostasis, 1990)
Aspirin has been shown to be beneficial in the prophylaxis of arterial thromboembolic disease. The rationale for its use as an antithrombotic drug lies in its inhibition of thromboxane A2- dependent platelet function. However, the effect of aspirin on coagulation and fibrinolysis during chronic therapy has not been studied. We have measured a range of haemostatic and platelet functions in 49 patients with transient ischaemic attacks randomly allocated to aspirin 300 mg a day, aspirin 1,200 mg a day or placebo. All had been taking their allocated treatment for between 9 months and 4 years prior to investigation. Bleeding time was prolonged, serum thromboxane diminished and platelet aggregation to arachidonic acid but not ADP was abolished by both 300 mg and 1,200 mg aspirin, in a non-dose dependent fashion. Serum salicylate increased with the dose of aspirin ingested. No effect was seen with either dose of aspirin on urinary thromboxane and 6-keto-PGF1α excretion, or on coagulation. Patients taking 1,200 mg aspirin a day had a lower haemoglobin and packed cell volume, lower resting fibrinopeptide A concentration and lower basal plasminogen activator activity than those on placebo. Response to venous occlusion was norrnal in all groups. The results suggest 300 mg and 1,200 mg aspirin have an equivalent platelet inhibitory effect but 1,200 mg aspirin causes greater gastro-intestinal blood loss.